Analisis Akad Kerjasama Pertanian Perspektif Fikih Muamalah di Kabupaten Enrekang - Kurniawan, Muhammad Zuhud; Kara, Muslimin; M, Misbahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of agricultural partnership contracts from the perspective of fiqh muamalah in Enrekang Regency. The research focuses on the types of contracts used, their compliance with sharia principles, and the legal issues arising from their implementation. The research method employed is a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews, observation, and documentation. In addition to field data, the study is supplemented with literature sources, including books and scientific articles. The research results show that the most commonly used contracts in Enrekang Regency are muzara’ah and mukhabarah contracts.These contracts, in principle, represent forms of cooperation compliant with sharia, where profit-sharing is determined by mutual agreement between landowners and tenant farmers. Most partnership contract practices align with sharia principles, although some ambiguities persist, such as the phenomenon of ta’alluqul ‘uqud, or the interrelation of multiple contracts within a single transaction. As long as all parties consciously agree without coercion, these transactions can be deemed valid under sharia, in accordance with Allah’s statement in QS. An-Nisa’ (4:29). The study concludes that further education for farmers and investors is necessary to enhance their understanding of contracts compliant with fiqh muamalah, along with improvements in partnership systems to avoid elements of gharar and riba.